The rhetoric of disgust: considering public texts of disability - Loewen, Katherine A., author; Langstraat, Lisa, advisor; Doe, Sue, committee member; Bone, Jennifer, committee member (Colorado State University. Libraries, 2013)
While composition studies has paid heed to the topic of disability, it seldom explores the political and affective dimensions of disability studies, such as how bodies write and are written by the world. The purpose of this thesis is to explore discourses of disability by employing critical emotion studies, particularly theories of disgust, to rhetorically analyze two popular texts, Freaks directed by Tod Browning and Fears of Your Life by Michael Bernard Loggins. These texts illustrate how disgust works to both reaffirm and transform the normal/abnormal binary that maintains public perceptions of disability as a stigmatized and marginal identity. Largely, this analysis emphasizes the role of non-academic, non-institutional, and non-standard discourses of disability to revitalize composition's foundational commitment to supporting human agency and social change.
Keywords: cultural studies; emotion theory; disability studies